2022
DOI: 10.3389/fnmol.2022.931704
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Oxidative Stress by Long Non-coding RNAs in Central Nervous System Disorders

Abstract: Central nervous system (CNS) disorders, such as ischemic stroke, Alzheimer’s disease, Parkinson’s disease, spinal cord injury, glioma, and epilepsy, involve oxidative stress and neuronal apoptosis, often leading to long-term disability or death. Emerging studies suggest that oxidative stress may induce epigenetic modifications that contribute to CNS disorders. Non-coding RNAs are epigenetic regulators involved in CNS disorders and have attracted extensive attention. Long non-coding RNAs (lncRNAs) are non-codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 128 publications
0
4
0
3
Order By: Relevance
“…Though the above study shows a positive interaction between lncRNAs, SIRT1, and OM, a recent study on centenarians showed that dysregulated lncRNAs are the possible preventive factors in healthy aging in the longevous population [66]. This could be due to the fact that lncRNAs have been observed to mediate oxidative stress in several disorders [67]. The silencing of several lncRNAs has been shown in the recovery of neuronal activities.…”
Section: Discussionmentioning
confidence: 85%
“…Though the above study shows a positive interaction between lncRNAs, SIRT1, and OM, a recent study on centenarians showed that dysregulated lncRNAs are the possible preventive factors in healthy aging in the longevous population [66]. This could be due to the fact that lncRNAs have been observed to mediate oxidative stress in several disorders [67]. The silencing of several lncRNAs has been shown in the recovery of neuronal activities.…”
Section: Discussionmentioning
confidence: 85%
“…ROS is a metabolic by-product in biological systems that has a double-edged role on cell function depending on its concentration. While low level of ROS can have a positive effect, excessive ROS can cause damage to cells [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…A lot of research has been carried out so far on long non-coding RNAs (lncRNAs) involved in oxidative stress and inflammation-related disorders with some already existing reviews such as those of Wang Y. et al (2019) ; Soudeh et al (2020) ; Kalhori et al (2021) ; Xu and Zhang (2022) ; as well as Zhao et al (2021) which outline lncRNAs with some of their mechanisms of action in oxidative stress and inflammation-related disorders. This section reviewed a few which have been investigated with natural products and expressed in disorders such as diabetes, cancers, autoimmune diseases, and neurodegenerative diseases (Parkinson’s diseases and Alzheimer’s diseases) with more equally found in Table 1 .…”
Section: Non-coding Rnasmentioning
confidence: 99%